2021
DOI: 10.1111/hsc.13356
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a community‐based food education programme on dietary pattern in patients with type 2 diabetes: Results of a pilot randomised controlled trial in Portugal

Abstract: The purpose of this study was to analyse the effects of a food education programme, with easy-to-implement strategies integrated in a community-based exercise programme, on dietary pattern of patients with type 2 diabetes (T2D). Thirty-three patients (65.4 ± 5.9 years old) were engaged in a 9-month randomised controlled trial: a supervised exercise programme (control group [CON]; n = 15; combined exercise; three sessions per week; 75 min per session) or the same exercise programme plus a concomitant 16-week fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…In what concerns nutritional intervention, there is a lack of easy-to-implement strategies among community settings in order to develop the capacity for self-management of diet 20 . Previous findings from our research team showed that a food education programme improved the dietary pattern of T2D patients through significant changes in polyunsaturated fat intake and servings of vegetables per day 21 .…”
Section: Introductionmentioning
confidence: 98%
“…In what concerns nutritional intervention, there is a lack of easy-to-implement strategies among community settings in order to develop the capacity for self-management of diet 20 . Previous findings from our research team showed that a food education programme improved the dietary pattern of T2D patients through significant changes in polyunsaturated fat intake and servings of vegetables per day 21 .…”
Section: Introductionmentioning
confidence: 98%